2019
DOI: 10.1038/s41598-019-52471-4
|View full text |Cite
|
Sign up to set email alerts
|

The shape of disposable diaper affects spontaneous movements of lower limbs in young infants

Abstract: This study examined the characteristics of young infants’ lower limb spontaneous movements based on differences in shape of diapers. Twenty-seven healthy infants (103 ± 16.3 days old) were enrolled in this study. We measured the spontaneous movements of their lower limbs in four conditions (Naked, wearing Normal type diapers, wearing Type A diapers, and wearing Type B diapers). The Normal diaper has a wider waist belt than the Type A diaper, and the Type B diaper has a narrower crotch area than the Type A diap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The relationship between wearing diapers and gait parameters in toddlers based on the aforementioned results suggests that wearing diapers may lead to unstable and inefficient gait patterns. This is consistent with previous studies reporting that wearing diapers has an adverse effect on the development of lower limb movements in infants 17 , 18 , 24 . In addition, our study is the first to reveal the joint dynamics when wearing diapers and the effect of different bulk stresses on lower limb gait in toddlers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The relationship between wearing diapers and gait parameters in toddlers based on the aforementioned results suggests that wearing diapers may lead to unstable and inefficient gait patterns. This is consistent with previous studies reporting that wearing diapers has an adverse effect on the development of lower limb movements in infants 17 , 18 , 24 . In addition, our study is the first to reveal the joint dynamics when wearing diapers and the effect of different bulk stresses on lower limb gait in toddlers.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported that wearing a disposable diaper restrains an infant’s movements and mobility, thereby reducing the amount of their physical activity and restricting motor development. Gima et al demonstrated that the shape of the diaper affects the spontaneous movements of the lower limbs in young infants 17 . Additionally, Cole et al concluded that wearing diapers may decrease the gait proficiency in toddlers aged between 13 and 19 months 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the development of inappropriate postures and positions as a result of inappropriate diapers, premature babies are at risk for long-term developmental disorders of musculoskeletal deformities, including lower extremity movement disorders, postural disorders such as frog legs, and delayed gross motor function. 7,16,17 A flattened posture of the lower legs and hips, resulting in delays in walking and crawling, is of particular concern in the diaper area. When the newborn is positioned prone or supine, the flattened posture caused by excessive hip rotation gives a “frog-legged” image.…”
Section: Impact Of Using Diapers In Preterm Infantsmentioning
confidence: 99%
“…7,17 Interventions to prevent this event include reducing the angle of rotation of the hips and making the knees aligned through the use of positioning aids (Figure 2). 17…”
Section: Impact Of Using Diapers In Preterm Infantsmentioning
confidence: 99%
See 1 more Smart Citation